Adaptive change of institutions and dynamic governance of the tragedy of the tourism commons: Evidence from rural China. (December 2022) - Su, Yiqing; Li, Rui; Ma, Hui; Huang, Liuzhao
Abstract: Rural tourism has massively contributed to the progress of developing countries. However, excessive appropriation of limited tourism commons by the residents of tourist destinations over the course of tourism development constantly causes conflicts. These conflicts are triggered by the attribute of tourism commons as common pool resources; therefore, these conflicts essentially fall within the tragedy of the tourism commons. To resolve this tourism conflict represented by the tragedy of the tourism commons, a dynamic institutional design is needed that is adaptable to local conditions. This study takes Yuanjia Village—located in Shaanxi Province, China—as research object, and explores how Yuanjia Village realizes the dynamic governance of the tragedy of the rural tourism commons through the adaptive change of institutions, thus solving tourism conflicts. The institutions of Yuanjia Village have followed a path of adaptive change from co-production to co-creation and have identified the meanings of adaptive institutional change for the sustainable development of rural tourism. The development of rural tourism not only depends on good natural resource endowment and sufficient material investment, it must also be realized by continually optimizing cooperation between residents in a constantly changing environment. This paper establishes a conceptual basis and case study for future research on the relationship between institutions and rural tourism development.